(untitled) (Veterinary Science, 2020)
Leptospirosis is an infectious disease caused by Leptospira spp.. It is not usually considered as part of the differential diagnosis in sick cats, which is a significant risk in public health. Two cases of clinical leptospirosis in cats confirmed by serology are described. They are both European mixed breed, a 13-year-old female and a 7-year-old male, castrated and from two towns in the south of Santa Fe province. They are hunters with indoor/outdoor habits, and live with other animals. They were admitted into the clinic due to progressive weight loss, anorexia and hematuria. Blood tests were taken to obtain complete blood count, blood biochemistry and serological determinations were performed to detect Leptospira spp, feline immunodeficiency virus (FIV) and feline leukemia (FeLV). The results of the hemogram, the hepatic and renal profile together with the symptomatology, comfirmed the suspicion of an alleged leptospirosis. Antibodies against Leptospira spp were detected in both cats and, in the male for FIV as well. Using the microscopic agglutination technique (MAT), the following serovars and antibody titles were detected in the female: Pomona 1: 100, Icterohemorragiae: 1: 200, Canicola: 1: 200 and Grippothyphosa 1: 100 and in the male: Pomona 1: 6400, Icterohaemorrhagiae 1: 400 and Bratislava 1:50. A treatment with benzathinic and procaine benzylpenicillin and streptomycin 10000 IU/l/kg subcutaneously was applied every 24 hours for 20 days as an antibacterial therapy. Subsequently, oral 10 mg/kg doxycycline was used for 30 days with the addition of a vitamin complex. In the male, ampicillin sulbactam 20 mg/kg was administered intravenously every 12 hours. In both cases the evolution was favorable, confirming the clinical efficiency of beta-lactam antibiotics for the disease treatment. The female recovered. In the male, antibacterial chemotherapy was interrupted and died.